PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TIM PENDENGAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 29 SOLOK SELATAN - Fauziah, Melda; Husna, Husna; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACTThe background of this research is the lower ability comprehension of mathematical concept for students. The students on the study math are out of less focus during a learning and still there only separated of students that memorize the formula. The purpose of this research is to determine whether ability comprehension of mathematical concept for students by applying active learning strategy type listening team were better than implementasi of conventional learning students for grade IX SMPN 29 Solok Selatan. The type of research is experimental by using Randomized on the subject. The instrument of this research is the comprehension of mathematical concept test. The technique of data analysis is using t-test one side with help Minitab. Based on the data analysis results have sampel class distribution normal and homogeneous to level Î±. The result that obtained P-value = Â 0,01 Î± then this research is accepted hypothesis. Inferential that the ability comprehension of mathematical concept for student by applying active learning strategy type listening team is better than implementasi conventional learning.